E-127 Clopidogrel hyper-responsiveness is associated with hemorrhagic complications post cerebrovascular stenting procedures. (4th August 2020) - Muram, S; Panchendrabose, K; Eagles, M; Suheel, M; Mitha, A
Abstract : Background: Anti-platelet therapy is an important part of the treatment regimen in patients who are receiving a cerebrovascular stent, in order to reduce the incidence of thromboembolic complications. However, there is a known variation in patient response to anti-platelet medications. Theoretically, patients with decreased responsiveness may be at increased risk of ischemic complications while those with increased responsiveness may be at a heightened risk of bleeding. The objective of this investigation was to determine if patients with an increased response to clopidogrel were at an increased risk of developing post-procedural hematomas. Methods: A prospective Research Ethics Board (REB) approved study was performed on consecutive patients undergoing endovascular placement of a cerebrovascular stent at the Foothills Medical Centre in Calgary, Alberta from 2019–2020. Inclusion criteria were patients over 18 years of age, and on dual anti-platelet therapy consisting of aspirin and clopidogrel for at least 3 days prior to the procedure. Platelet function testing was performed on blood samples taken before insertion of the stent using whole blood impedance aggregometry to determine the responsiveness to aspirin and clopidogrel. As per the REB protocol, treating neurointerventionalists were blinded to the aggregometry results. The primary study endpoint was the development of hemorrhagic complications during or after the procedure. Parametric and receiver operator curve analysis was used to assess for predictors of our primary outcome. Results: To determine the cut-offs for ASA and clopidogrel responsiveness, whole blood aggregometry was first performed on 25 control patients who were not on anti-platelet agents. Subsequently, 50 consecutive patients undergoing cerebrovascular stenting procedures fit our inclusion criteria. 7 (14.0%) of these patients developed a hematoma either intracranially (n=1) or at the puncture site (n=6). Age, gender, smoking status, access site, or stent location were not associated with hemorrhagic complications. Based on our controls, ASA hyper-responders could not be identified using whole blood aggregometry due to the normal response being 0–1 ohms. With these cut-offs, however, 49 (98%) of our patients were responsive to aspirin. Using whole blood aggregometry on patients receiving a cerebrovascular stent, the optimal electrical impedance value was identified as < 1 ohm (sensitivity 71.43%, specificity 74.42%, area under the curve 0.82) for clopidogrel hyper-responders. Of the 16 patients who had an impedance aggregometer value of 0–1 ohms for clopidogrel response, 5 (31.3%) of them developed a hematoma, while only 2 (6.7%) out of the 30 patients who had an aggregometer value of >2 ohms developed a hematoma. This association was found to be statistically significant (p=0.016). Conclusion: Dual anti-platelet therapy is an important part of the treatment regimen in any patient who receives a cerebrovascular stent, but there are variations in patient response to these medications. Our study suggests that patients who have an increased response to clopidogrel may be at a higher risk of developing hemorrhagic complications. Disclosures: S. Muram: None. K. Panchendrabose: None. M. Eagles: None. M. Suheel: None. A. Mitha: None.